2017
DOI: 10.1186/s13287-017-0685-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment evaluation of Wharton’s jelly-derived mesenchymal stem cells using a chronic salpingitis model: an animal experiment

Abstract: BackgroundThe present study was conducted to evaluate new methods to repair the reproductive function of the oviduct, thereby allowing gametes to combine and grow in vivo under natural circumstances.MethodsSixty pathogen-free female New Zealand rabbits were divided into three groups: a wild-type group, an untreated control group, and a treatment group. Disposable sterile newborn sputum suction tubes were inserted into the urogenital tract to instill an Escherichia coli suspension into the uterine cavity to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Salpingitis model studies on other experimental animals such as rat and rabbit have been reported ( Luo et al., 2015 ; Li et al., 2017 ; Liao et al., 2019 ). The more commonly used are methods of pathogenic microorganism modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Salpingitis model studies on other experimental animals such as rat and rabbit have been reported ( Luo et al., 2015 ; Li et al., 2017 ; Liao et al., 2019 ). The more commonly used are methods of pathogenic microorganism modeling.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can also provide a variety of cytokines and chemokines, including epidermal growth factor (EGF), insulin-like growth factor binding protein (IGFBP), and insulin-like growth factor-1 (IGF), for target cells through paracrine processes (Islam, et al 2016;Zhang, et al 2016). Several studies have suggested that MSCs stimulate the expression of anti-inflammatory cytokines, such as IL10 and tumor necrosis factor (TNF)-α, which improve the function of damaged fallopian tubes by decreasing the level of inflammatory factors (Li, et al 2017;Liao, et al 2019). These secretomes have shown immense potential for the treatment of damaged endometrium by promoting endometrial proliferation and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that pregnancy rate increased significantly, and these effects were attributed to the anti-inflammatory and anti-apoptotic properties of hUC-MSC (Liao et al, 2019). In addition, Li et al (2017) observed that WJ-MSCs restored the epithelial structure of the FT and concentration of TNF was decreased significantly in the treatment group with WJ-MSCs, and they also reported that WJ-MSCs improved the secretion of oviduct glycoprotein and fertility partially in rabbits with chronic salpingitis. Furthermore, Ebrahim et al (2018) revealed that hUC-MSC-EV alone or in combination with estrogen significantly reduced intrauterine adhesions in female rats due to decrease in inflammatory cytokines (TNF-α, IL-1, IL-6) and fibrotic markers (RUNX2, TGF-β, collagen-I).…”
Section: Application Studies Of Mesenchymal Stem Cell-derived Exosomesmentioning
confidence: 95%